1979
DOI: 10.1111/j.1471-0528.1979.tb10611.x
|View full text |Cite
|
Sign up to set email alerts
|

Red Cell Mass During and After Normal Pregnancy

Abstract: Red cell mass, derived from plasma volume and haematocrit, was calculated serially in 45 healthy women during pregnancy and 4 to 6 months after delivery. Compared to the non-pregnant, postpartum value there was a reduction of approximately 100 ml at 12 weeks gestation. An increase in red cell mass occurred thereafter: at 36 weeks gestation values 180 ml greater than the non-pregnant were found. Iron and folic acid supplements almost double,d this increment to 349 ml of red cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
82
1
1

Year Published

1993
1993
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(86 citation statements)
references
References 14 publications
2
82
1
1
Order By: Relevance
“…Previous studies have used Hb cut-off values of either 10 gadl (Lao et al, 1996), 11 gadl (Singh et al, 1998) or 12 gadl (Kuvibidila et al, 1994). Although it has been suggested that the haemodilution effect of pregnancy is still apparent at 6 ± 8 weeks postpartum (Taylor & Lind, 1979), our ®ndings showed that the mean Hb level of subjects had increased to ! 12 gadl by 6 weeks postpartum and remained fairly constant until 6 months postpartum.…”
Section: Discussioncontrasting
confidence: 55%
“…Previous studies have used Hb cut-off values of either 10 gadl (Lao et al, 1996), 11 gadl (Singh et al, 1998) or 12 gadl (Kuvibidila et al, 1994). Although it has been suggested that the haemodilution effect of pregnancy is still apparent at 6 ± 8 weeks postpartum (Taylor & Lind, 1979), our ®ndings showed that the mean Hb level of subjects had increased to ! 12 gadl by 6 weeks postpartum and remained fairly constant until 6 months postpartum.…”
Section: Discussioncontrasting
confidence: 55%
“…Later, it again decreases. Significant elevation has been documented between measurements of hemoglobin taken at 6-8 weeks postpartum and those taken at 4-6 months postpartum, indicating that it takes at least 4-6 months post pregnancy, to restore the physiological dip in hemoglobin to the nonpregnant values [7].…”
mentioning
confidence: 99%
“…An increase in the red cell mass during pregnancy has been reported [25] and we previously ascertained that the number of pump units in young erythrocytes is higher than that in old ones [15]. However, in this assay, neither the number nor function of the pump have any correlation with the mean corpuscular volume (data not shown).…”
Section: Discussionmentioning
confidence: 65%